Maternal diet quality before pregnancy and risk of childhood leukaemia. Issue 8 (11th October 2016) - Singer, Amanda W.; Carmichael, Suzan L.; Selvin, Steve; Fu, Cecilia; Block, Gladys; Metayer, Catherine
Abstract: Previous studies on maternal nutrition and childhood leukaemia risk have focused on the role of specific nutrients such as folate and have not considered broader measures of diet quality, which may better capture intake of diverse nutrients known to impact fetal development. We examined the relationship between maternal diet quality before pregnancy, as summarised by a diet quality index, and risk of childhood acute lymphoblastic leukaemia (ALL) and acute myeloid leukaemia (AML) in a case–control study in California. Dietary intake in the year before pregnancy was assessed using FFQ in 681 ALL cases, 103 AML cases and 1076 matched controls. Conditional logistic regression was used to estimate OR and 95 % CI for diet quality continuous score and quartiles (Q1–Q4). Higher maternal diet quality score was associated with reduced risk of ALL (OR 0·66; 95 % CI 0·47, 0·93 for Q4 v. Q1) and possibly AML (OR 0·42; 95 % CI 0·15, 1·15 for Q4 v. Q1). No single index component appeared to account for the association. The association of maternal diet quality with risk of ALL was stronger in children diagnosed under the age of 5 years and in children of women who did not report using vitamin supplements before pregnancy. These findings suggest that the joint effects of many dietary components may be important in influencing childhood leukaemia risk.